TINGKAT KECERDASAN PADA ANAK DITINJAU DARI PERBEDAAN GENDER - Anggraeni Mashinta Sulistyani (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
Abstract: Gender is the differences of the roles, functions and responsibilities between women and men resulting from socio-cultural construction and can alter from time to time. Although men and women have differences in their physical, emotional, and intellectual, but actually there is no evidence relating to it. The level of intelligence can not be explained by biological differences. One thing that can be considered as a determining factor is the level of intelligence of the brain. The brain has several important parts which has each function. Some parts of the brain such as the cerebral cortex is composed of several components which is very influential in controlling the movement of conscious and cognitive abilities, as well as information of processing, language and speech, lateralization, emotions and consciousness. At this stage of development, there is a difference between the development of the brains of women and men. Some parts of the female brain tends to grow faster than the development of the male brain. Differences in brain development is resulting in different levels of development of intelligence even between women and men. It can reinforce that women have some advantages, especially the level of intelligence than men. Thus, there is no gender difference in environmental terms of social life. Kata Kunci: Tingkat Kecerdasan, Anak, dan Perbedaan Gender